Kajian KAJIAN MINAT BELI ULANG SECARA ONLINE PADA GENARASI Z DENGAN PERCEIVED RISK, KEPERCAYAAN, DAN GAYA HIDUP SEBAGAI VARIABEL ANTESEDEN - Anjas Kridho Asmoro; Audita Nuvriasari (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This research analyses the effect of perceived risk, trust, and lifestyle towards online repurchase intention on gen z using Shopee as a marketplace. Sampling technique used purposive sampling and 100 respondents in the research sample in total. Hypothesis result of this research is proven that perceived risk has no significant affect towards online repurchase intention. It refers that perceived risk variable isn't affected to online repurchase intention on gen Z. Hence, the opposite of previous statement, trust and lifestyle have positive influenced and significantly towards online repurchase intention. The higher trust that given and the more gen Z's lifestyle fitted with online purchase behavior in Shopee marketplace, would likely increase online repurchase intention. Determination test results show that perceived risk, trust and lifestyle affected to 51,8% online repurchase intention.